THE IDEAS OF SCIENCE AND EDUCATION IN THE RELIGIOUS AND SECOND TEACHINGS OF KHAKIM AT-TERMIZI AND ABU ISA AL-TERMIZI - A. Mukhtarov (Journal Park Publishing, 2025)
Many medieval scholars paid great attention to the development of religious sciences, as well as secular knowledge in various fields of science. One of the great scientists who created works of world significance, the famous al-Hakim at-Termizi, Abu Isa al-Termizi, wrote many books on internal and external knowledge. In his works, he expressed unique views on the history of Islam, its teachings, the theory of Sufism, the science of hadith, morality and various sects. In his work, the protection of the interests of society, the pursuit of human excellence, his honor, the advancement of science and education, his ideas, theoretical views have not lost their relevance today. He left us with a rich and great scientific legacy.
Keywords: Hakim at-Termizi, Abu Isa al-Termizi, secular and religious knowledge, internal and external knowledge, human perfection, hadith science, enlightenment, history of Islam, Sufi theory, ethics